2021
DOI: 10.1021/acs.jpcc.1c03182
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Metal-Ion Replacement on the Phase Stabilization of Cubic All-Inorganic Cesium Lead Halide Perovskites: an Ab Initio Thermodynamic Formalism for Solution-Processed Cation Doping

Abstract: All-inorganic metal-halide perovskites are demonstrating good prospects toward long-term stability and high efficiency in the field of perovskite photovoltaics. Stemming from CsPbI3, compositional engineering via cation and anion doping has been widely adopted to improve device performance, especially the perovskite phase stability. In contrast to anion doping with smaller halogens, experimentally observed cation-doping effects on the perovskite stability cannot be simply explained or predicted by the geometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 96 publications
0
14
0
Order By: Relevance
“…elements. 14 Furthermore, halide double perovskites (HDPs) with 2ABX 3 → A 2 B 2 X 6 stoichiometry extend accessible B-site metals, allowing for the mixed-metal HDPs A 2 BB′X 6 (B = Au + , Ag + , Tl + , Na + , K + ; B′ = Au 3+ , Tl 3+ , Bi 3+ , In 3+ , Sb 3+ ) 15–17 and vacancy-ordered double perovskites A 2 B□X 6 (B = Sn 4+ , Te 4+ , Pd 4+ , etc. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…elements. 14 Furthermore, halide double perovskites (HDPs) with 2ABX 3 → A 2 B 2 X 6 stoichiometry extend accessible B-site metals, allowing for the mixed-metal HDPs A 2 BB′X 6 (B = Au + , Ag + , Tl + , Na + , K + ; B′ = Au 3+ , Tl 3+ , Bi 3+ , In 3+ , Sb 3+ ) 15–17 and vacancy-ordered double perovskites A 2 B□X 6 (B = Sn 4+ , Te 4+ , Pd 4+ , etc. ).…”
Section: Introductionmentioning
confidence: 99%
“…elements. 14 Furthermore, halide double perovskites (HDPs) with 2ABX 3 / A 2 B 2 X 6 stoichiometry extend accessible B-site metals, allowing for the mixed-metal HDPs A 2 BB ′ X 6 (B = Au + , Ag + , Tl + , Na + , K + ; B ′ = Au 3+ , Tl 3+ , Bi 3+ , In 3+ , Sb 3+ ) [15][16][17] and vacancy-ordered double perovskites A 2 B,X 6 (B = Sn 4+ , Te 4+ , Pd 4+ , etc.). 18,19 The homovalent substituting Sn 2+ or Ge 2+ for toxic Pb 2+ in ABX 3 single perovskites gives rise to instability against oxidation, 20,21 whereas the heterovalent replacement by mono-and tri-valent cations in A 2 BB ′ X 6 (ref.…”
Section: Introductionmentioning
confidence: 99%
“…Organic-inorganic metal halide perovskites are considered the most promising materials for next-generation photovoltaic technology owing to their outstanding optoelectronic properties, such as a long charge carrier diffusion length, high carrier mobility, a tunable optical bandgap, low trap density, higher optical absorption, low exciton binding energy, [1][2][3][4] lowtemperature solution processibility, and cost-effective fabrication approaches. The highest certified power conversion efficiency (PCE) of perovskite solar cells (PSCs) has rapidly increased from 3.8% to 25.5% 5,6 in the past few years, which is close to the state-of-the-art Si-based solar cell performance.…”
Section: Introductionmentioning
confidence: 99%
“…Using DFT, Kye et al also found α-CsPbI 3 to have a negative enthalpy of formation, though it was less negative than δ-CsPbI 3 , i.e., the α-polymorph is only metastable with respect to the δ-phase. 51 The low temperature heat capacity of CsPbI 3 was only reported from 0.4 up to 150 K by Evarestov et al 52 As a sidenote, the Cs 2 PbX 4 and CsPb 2 X 5 compounds, which were studied using time-dependent density functional theory (TD-DFT), do not exist as bulk compounds for X = I, 53 though there can be two-dimensional materials formed via nonambient pressure routes. 54 Compared to the two systems discussed in supra, practically nothing is known about the BiI 3 −PbI 2 system.…”
Section: ■ Introductionmentioning
confidence: 99%
“…58 Kye et al found similar results. 51 For thin films, the metastability of α-CsPbI 3 with respect to δ-CsPbI 3 upon Bi 3+ -doping was also experimentally proven: above 393 K, the films turn into the δ-CsPbI 3 variant. 59 ■ METHODS Synthesis.…”
Section: ■ Introductionmentioning
confidence: 99%